Descriptors for genetic markers technologies - Vicente, M. Carmen de; Metz, T.; Alercia, A. (International Plant Genetic Resources Institute, 2004)
This document is targeted to researchers using genetic marker technologies to generate and exchange genetic marker data that are standardized and replicable. This initial proposed set of descriptors was reviewed widely by international experts from national research institutions, universities and CGIAR centres, and their comments and contributions were included through several iterations of the document. This first official version of the list is now being published by IPGRI to encourage application of the descriptors to current research projects and to stimulate further refinement of the standards.